2016
DOI: 10.17957/tpmj/16.3254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tamsulosin on Stentrelated Symptoms; A Prospective Study

Abstract: ORIGINAL PROF-3254 ABSTRACT… Introduction: Cystoscopic intraluminal placement of ureteral stents has become a routine practice in urology. Ureteral stents preserve urine flow from the kidney to the bladder in cases of ureteral obstruction (intrinsic or extrincis). In patients with obvious ureteral obstruction, the placement of a ureteral stent will restart urine transport and protect the kidney from possible risks. Ureteral stents are troublesome in some patients and causes LUTS. Study Design: Prospective rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Postoperative complications outcome is also affected by the administration of postoperative alpha-blockers 19 , 20 . It was found that endoscopic treatments without the administration of adjunctive alpha-blockers are associated with a higher probability of complications 2 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications outcome is also affected by the administration of postoperative alpha-blockers 19 , 20 . It was found that endoscopic treatments without the administration of adjunctive alpha-blockers are associated with a higher probability of complications 2 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…15,18 Postoperative complications outcome is also affected by the administration of postoperative alpha-blockers. 19,20 It was found that endoscopic treatments without the administration of adjunctive alpha-blockers are associated with a higher probability of complications. 2,21 This was shown by the forest plot, where the adjunctive alpha-blocker gives a protective effect from postoperative complications with RR = 0.41 (95% CI, 0.27-0.61).…”
Section: Discussionmentioning
confidence: 99%
“…In group A at baseline the mean of IPSS score was 9.17 (SD 1.53), the QoL score was 2.1 (SD 0.86) and Total IPSS + QoL questionnaire score 11.28(SD 1.6), but at stent removal the mean scores were 14.41 (SD 3.34) for IPSS, and 2.76 (SD 1.12) for QoL score and Total IPSS + QoL questionnaire score 17.24 (SD 3.25) 9. The findings of other study are similar to our study.…”
mentioning
confidence: 94%
“…2,6 Alpha adrenergic receptor like α1A and α1D have been documented to be distributed the in the lower urinary tract and the distal ureter and the use of alpha adrenergic receptor blockers like Tamsulosin have shown considerable promise in treating the stent related symptoms. [7][8][9] This study, was done in an effort to determine the effect of tamsulosin in improving double-J stent related symptoms and QoL following ureteral stent placement.…”
Section: Introductionmentioning
confidence: 99%